Resettlement Multiculturality - Słowiński, Marcin (Journal of Applied Cultural Studies, 2016)
The aim of the study is to present the concept of resettlement multiculturality. The multiculturality of displaced persons, the kind characterising resettlement in Western Poland, was not brought about spontaneously and is governed by entirely different principles. At this point one should contemplate the methods that assisted in the management of a city that is multicultural in character due to residents having been resettled, a city whose identity has not fully formed. Such a measure could also bring empirical confirmation uprooting occurred in the fourth generation. Presenting the concept of resettlement multiculturality the author is making use of – among other things – memory studies, Pierre Bourdieu’s theory of capital and his concepts of habitus, field and game, and the research of Geert Hofstede.